3D bioprinting of engineered exosomes secreted from M2-polarized macrophages through immunomodulatory biomaterial promotes in vivo wound healing and angiogenesis - Sayan Deb Dutta; Jeong Man An; Jin Hexiu; Aayushi Randhawa; Keya Ganguly; Tejal V. Patil; Thavasyappan Thambi; Jangho Kim; Yong-kyu Lee; Ki-Taek Lim (Bioactive Materials)
Biomaterial composition and surface charge play a critical role in macrophage polarization, providing a molecular cue for immunomodulation and tissue regeneration. In this study, we developed bifunctional hydrogel inks for accelerating M2 macrophage polarization and exosome (Exo) cultivation for wound healing applications. For this, we first fabricated polyamine-modified three-dimensional (3D) printable hydrogels consisting of alginate/gelatin/polydopamine nanospheres (AG/NSPs) to boost M2-exosome (M2-Exo) secretion. The cultivated M2-Exo were finally encapsulated into a biocompatible collagen/decellularized extracellular matrix (COL@d-ECM) bioink for studying angiogenesis and in vivo wound healing study. Our findings show that 3D-printed AGP hydrogel promoted M2 macrophage polarization by Janus kinase/signal transducer of activation (JAK/STAT), peroxisome proliferator-activated receptor (PPAR) signaling pathways and facilitated the M2-Exo secretion. Moreover, the COL@d-ECM/M2-Exo was found to be biocompatible with skin cells. Transcriptomic (RNA-Seq) and real-time PCR (qRT-PCR) study revealed that co-culture of fibroblast/keratinocyte/stem cells/endothelial cells in a 3D bioprinted COL@d-ECM/M2-Exo hydrogel upregulated the skin-associated signature biomarkers through various regulatory pathways during epidermis remodeling and downregulated the mitogen-activated protein kinase (MAPK) signaling pathway after 7 days. In a subcutaneous wound model, the 3D bioprinted COL@d-ECM/M2-Exo hydrogel displayed robust wound remodeling and hair follicle (HF) induction while reducing canonical pro-inflammatory activation after 14 days, presenting a viable therapeutic strategy for skin-related disorders.